Informatyzacja postępowania administracyjnego postępuje. Kolejne zmiany w k.p.a. - Chmieliński, Paweł (Kwartalnik Prawa Publicznego, 2014)
The Act of 10 January 2014 amending the Act on computerization of operation of entities performing public tasks and some other acts has amended the provisions of the Code of Administrative Proceedings. The aim of article is to – preliminary – appraise the changes, which can be divided into two types. The first includes corrective provisions, which broaden the possibility of using the electronic document form. The second type introduces new solutions to the Code, such as the fiction of electronic service.